PENGARUH STRATEGI INTENSIFIKASI DAN EKSTENSIFIKASI SERTA KEBIJAKAN PEMERINTAH TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH DI DINAS PENDAPATAN KABUPATEN NIAS BARAT - Lahagu, Kasihniat Gustiani; Saragih, Joana L.; Pangaribuan, Jonner (Jurnal Riset Akuntansi & Keuangan, 2025)
This research aims to test how significantly the Intensification, Extensification, and Government Policy Strategies influence the increase in Regional Original Income. The sampling technique used is saturated sampling, where all members of the population are included as samples. The data was obtained from the Regional Financial and Asset Management Agency (BPKPD) of Nias Barat Regency, covering the years from two thousand twenty-one to two thousand twenty-three. The analysis technique employed in this study is Multiple Linear Regression, with a significance level of five percent. Based on the results of the t-test, it shows that the Intensification Strategy has a positive and significant effect on Local Revenue, with a calculated t-value of two point two seventy-seven, which is greater than the t-table value of two point zero fourteen, and a significance level of zero point zero four eight, which is less than zero point zero five. Extensification also has a positive and significant effect on Local Revenue, with a calculated t-value of two point one sixty-one, which is greater than the t-table value of two point zero fourteen, and a significance level of zero point zero three six, which is less than zero point zero five. Additionally, Government Policy has a positive and significant effect on Local Revenue, with a calculated t-value of five point four eighty, which is greater than the t-table value of two point zero fourteen, and a significance level of zero point zero zero zero, which is less than zero point zero five. Furthermore, the F-test results indicate that the Intensification Strategy, Extensification, and Government Policy, when considered together, have a positive and significant effect on Local Revenue, with a calculated F value of seventy-three point seven fifty-four, which is greater than the F-table value of two point eighty, and a significance level of F at zero point zero zero zero, which is less than alpha zero point zero five.